Wanita Dalam Film Setan Jawa - wibisono, aryo bayu (Program Studi Desain Komunikasi Visual. Fakultas Arsitektur dan Desain Jalan Raya Rungkut Madya, Gn.Anyar, Surabaya, Jawa Timur 60294, 2023)
Indonesia is a unique country, which has thousands of customs and traditions. The mystical encounter has become an interesting reality in the customs and traditions of Indonesia. The film Satan Jawa, which was initiated by filmmaker Garin Nugroho, looks at the paradigm and mystical encounter that exists in the reality of Indonesian society. That film is “Satan Jawa”, which is a colossal mystical film set in the Gamelan Orchestra. Interestingly, this film is not shown in every cinema, YouTube or paid film portals. Therefore, the reviewer's perspective will give a different reaction in each perspective. The aim of this research in the film Satan Jawa is to study a female figure, namely Asih as Setio's wife in the film Satan Jawa. Asih's central role in the film determines the plot of the film. The research method approach in the film Satan Jawa is through observation in the field, during the screening of the film Satan Jawa at the Theater Besar of the Indonesian Art Institute, Surakarta.